Diversifying Flower Farming Business Towards Agrotourism (Situational Analysis of Community Service Activities in Batu Malang City): Diversifikasi Bisnis Pertanian Bunga Menuju Eduagrowisata (Analisis Situasional Kegiatan Pengmas di Kota Batu Malang) - Syamsul Bahri; Nurida Finahari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Tourism based on the natural potential attraction is increasingly popular, especially for urban residents. This is based on a perceptive need for natural nuances which are believed to provide body refreshment through clean air. Agrotourism is one of this tourism type icons. Agrotourism adds its appeal to the attraction of expanses of plants (flowers, herbs and fruit) which are at various stages of growth and the activity of picking fruit directly from the trees. Although agrotourism also has several other common problems with natural tourism, this tourist attraction offers affordability for all groups. The fans have a wide spectrum, they don't know the season, and visitors always come even during the pandemic. This represents great potential for development efforts. Referring to the aim of agrotourism to expand knowledge (educational programs), experience, recreation and marketing of agronomic products, the general development of agrotourism potential is towards the commercialization of recreation and business management. The knowledge aspect (educational program) has not been touched much. Community service activities can be designed to develop agrotourism in the Sidomulyo Batu Malang area into the realm of eduagrotourism, namely tourism based on biology education, in line with the village's target of becoming an Educational Tourism Village. The aim of the activity can be directed at preparing activity partners to be able to display educational tourism attractions - edugrotourism - from nursery activities to marketing plant products, especially targeting children and students. This is in accordance with the latest education policy regarding Independent Learning and thematic curriculum.